URGENSI ANALISIS LINGKUNGAN STRATEGIS INTERNAL DAN EKSTERNAL PADA LEMBAGA PENDIDIKAN - Bakhtiar Bakhtiar (Program Studi Manajemen Pendidikan Islam, 2022)
Analysis of the internal and external environment of educational institutions is very important to do. Environmental analysis will determine the strengths, weaknesses and opportunities and threats faced by educational institutions in the current competitive era. The purpose of writing this article is to analyze the role and scope of the internal and external environment in educational institutions as well as the environmental analysis process model. The results of the analysis and discussion found: the role of observing the internal and external environment consists of: Policy Oriented Roles, Integrated Strategic Planning Roles, and Function Oriented Roles. Then an analysis of the internal environment in educational institutions is carried out on human resources, non-human resources, finance, markets, educational operations, research and development. While the analysis of the external environment of educational institutions is carried out on the macro and micro environment outside the educational institution, including demography, economics, social, culture, politics, technology, and competitors. Furthermore, in conducting strategic environmental analysis, it can be done using the SWOT analysis model.